Improving Patient Satisfaction: The Crucial Role of Lead Time and Room Facilities in Outpatient Services at Bandung Kiwari Hospital - Ikhsanawati, Annisa; Nu'man, Harits; Nurdin, Nurdin (Yayasan Gema Bina Nusantara, 2025)
Lead time and room facilities are critical factors influencing patient satisfaction with hospital services. This study aims to analyze the effects of lead time and room facilities on patient satisfaction in the Outpatient Department of Bandung Kiwari Hospital (RSUD Bandung Kiwari). The research employs a descriptive-verificative quantitative method, involving 150 respondents selected through purposive sampling from an outpatient population of 5,399 in July 2023. Data were collected using a Likert scale questionnaire. The results reveal that the majority of patients experienced lead times exceeding 60 minutes (65.3%), which is beyond the established standard. Conversely, room facilities were generally rated as highly satisfactory (81.95%), despite shortcomings in bathroom cleanliness. Overall patient satisfaction was categorized as good (79.26%), although lead time received a lower score (58%). Regression analysis indicates that lead time and room facilities have a significant simultaneous effect on patient satisfaction (F = 48.662, p = 0.000), with room facilities (β = 0.310, p = 0.000) having a greater partial influence compared to lead time (β = 0.234, p = 0.004). This study concludes that better management of lead time and improved quality of room facilities are essential for enhancing patient satisfaction. The findings highlight the importance of optimizing digital queue systems, improving cleanliness, and conducting regular evaluations through patient satisfaction surveys to ensure continuous service improvement.